Re-thinking Aesthetics - Berleant, Arnold (Filozofski vestnik, 2016)
This paper proposes a radical re-examination of the foundations of modern aesthetics. It urges that we replace the tradition of eighteenth century aesthetics, with its insistence on disinterestedness and the separateness of the aesthetic, and its problematic oppositions, such as the separation of sense from cognition. In their place it appeals to a more process-oriented, pluralistic account, one that takes note of varying cultural traditions in aesthetics, that recognizes the aesthetic as a complex of many forces and factors, and that considers the aesthetic as part of a complexity of values, including moral, practical, social, and political ones. It urges, further, an aesthetic-based criticism, not only of the arts, but of culture and knowledge. Central to this account is the idea of aesthetic engagement, which not only recognizes and extends the many connections of and in aesthetic experience, but invites our total involvement as active participants.